The Evolution Of Halal Research: A Bibliometric For 1996 – 2020 - Yumi Zuhanis Has-Yun Hashim; Anis Najiha Ahmad; Nurhusna Samsudin; Miratul Hayah Abd Lateef; Nurul Shahirah Majlan (USIM Press, 2024)
VOL. 27 NO. 3 (2022) Page (1-38)